PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN ARTIKULATE STORYLINE DI SMK PESANTREN TERPADU KABUPATEN MOJOKERTO - Sukirmiyadi Sukirmiyadi; Roziana Febrianita; Endang Sholihatin; Arista Pratama (Universitas Airlangga, 2021)
AbstractInteractive learning media with articulate storylines is one of the interactive and fun learning breakthroughs for students when studying from home during the covid-19 pandemic. Specific problems faced by partners of SMK Pesantren Terpadu Mojokerto Regency are: (a) Teachers have difficulty in making interactive learning media based on articulate storylines; (b) Teachers need tutors in transferring appropriate technology using articulate storyline software; (c) Teachers need assistants in transferring appropriate technology to the use of articulate storyline software. Solving the problem of partner needs is carried out with three strategies, namely: (a) knowledge improvement lectures to create interactive learning media based on information and communication technology; (b) training to increase the capacity of teachers in creating interactive learning media based on articulate storylines; (c) assistance to teachers in making interactive learning media based on articulate storylines. The method used in this community service program is a participatory method. In this method partners have the main role as planning managers, starting from the stage of identifying problems and needs. Transfer of knowledge and technology in the manufacture of interactive learning media with articulate storylines during the covid-19 pandemic at the Integrated Islamic Boarding School Vocational High School, Mojokerto Regency, encourages teachers to innovate to create innovative online learning media based on articulate storylines.Keywords: articulate storyline, interactive learning media AbstrakMedia pembelajaran interaktif dengan articulate storyline menjadi satu di antara terobosan pembelajaran yang interaktif dan menyenangkan bagi siswa saat belajar dari rumah saat pandemi covid-19. Permasalahan khusus yang dihadapi mitra SMK Pesantren Terpadu Kabupaten Mojokerto yaitu: (a) Guru kesulitan membuat media pembelajaran interaktif berbasis articulate storyline; (b) Guru membutuhkan tutor dalam mentransfer teknologi tepat guna penggunaan software articulate storyline; (c) Guru membutuhkan pendamping dalam mentransfer teknologi tepat guna penggunaan software articulate storyline. Penyelesaian masalah kebutuhan mitra dilakukan dengan tiga strategi yaitu: (a) ceramah peningkatan pengetahuan membuat media pembelajaran interaktif berbasis teknologi informasi dan komunikasi; (b) pelatihan meningkatkan kapasitas guru dalam membuat media pembelajaran interaktif berbasis articulate storyline; (c) pendampingan kepada guru dalam membuat media pembelajaran interaktif berbasis articulate storyline. Metode yang digunakan dalam program pengabdian masyarakat ini adalah metode partisipatif. Pada metode ini mitra mempunyai peran utama sebagai pengelola perencanaan, mulai dari tahap identifikasi masalah dan kebutuhan. Transfer pengetahuan dan teknologi dalam pembuatan media pembelajaran interaktif dengan articulate storyline pada masa pandemi covid-19 di Sekolah Menengah Kejuruan Pesantren Terpadu Kabupaten Mojokerto mendorong guru untuk berinovasi membuat media pembelajaran daring inovatif berbasis articulate storyline.Kata kunci: articulate storyline, media pembelajaran interaktif